Relationship between the clinical assessment of maxillary and mandibular complete denture stability and denture-bearing area towards the patientâs satisfaction level - Ritonga, Putri Welda Utami; Prabakaran, Luveena Loshini (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2018)
Introduction: The dentistâs evaluation of complete denture often differs from the patientâs evaluation. Dentists are more prioritising the clinical aspects of the dentures, such as vertical dimension, aesthetical, stability, and denture-bearing area, while patients are more prioritising their satisfaction based on aspects such as aesthetical, mastication, comfort, and phonetic ability. The purpose of this study was to determine the relationship between the stability of maxillary and mandibular denture-bearing area towards the complete denture patientâs satisfaction level. Methods: This study was a cross-sectional study with purposive sampling as the sampling method. The sample of this study was as much as 30 complete denture patient. The patients were interviewed using a questionnaire in each of the patientâs house, to obtain a more honest patientâs satisfaction assessment on the dentures, without being affected by any clinical environment and assessment. The interview was conducted before the clinical evaluation was performed. The statistical analysis was performed using the Fisherâs test. The stability of the denture-bearing area was evaluated clinically. Mastication ability and patientâs comfort were evaluated using a questionnaire. Result: A significant relationship was found between the stability of maxillary denture-bearing area towards mastication (p = 0.012), and the stability of mandibular denture-bearing area towards mastication (p = 0.029); while no significant relationship was found between the stability of maxillary denture-bearing area towards the patientâs comfort (p = 0,051), and the stability of mandibular denture-bearing area towards the patientâs comfort (p = 0,547). Conclusion: There was a relationship between the Â stability of maxillary and mandibular denture-bearing area towards the patientâs masticatory satisfaction level. However, the relationship between the Â stability of maxillary and mandibular denture-bearing area towards the patientâs comfort was not found.